The prevalence of pathologic skin picking in US adults - Keuthen, Nancy J.; Koran, Lorrin M.; Aboujaoude, Elias; Large, Michael D.; Serpe, Richard T. (Comprehensive psychiatry, 2010)
Despite increasing recognition of the potentially severe medical and psychosocial costs of pathologic skin picking (PSP), no large-sample, randomized investigation of its prevalence in a national population has been conducted. Two thousand five hundred and thirteen US adults were interviewed during the spring and summer of 2004 in a random-sample, national household computer-assisted phone survey of PSP phenomenology and associated functional impairment. Respondents were classified for subsequent analysis according to proposed diagnostic criteria. Of all respondents, 16.6% endorsed lifetime PSP with noticeable skin damage; 60.3% of these denied picking secondary to an inflammation or itch from a medical condition. One fifth to one quarter of those with lifetime PSP not related to a medical condition endorsed tension or nervousness before picking, tension or nervousness when attempting to resist picking, and pleasure or relief during or after picking. A total of 1.4% of our entire sample satisfied our criteria of picking with noticeable skin damage not attributable to another condition and with associated distress or psychosocial impairment. Pickers satisfying these latter criteria differed from other respondents in demographics (age, marital status) and both picking phenomenology and frequency.